Analisis Brand Awareness Pada Minuman Kekinian Di Kelurahan Rungkut Kidul: Studi Pada Usaha Minuman Lokal - Siti Aisyah Romadhoni; Muhadjir Anwar (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This research aims to analyze the level of brand awareness of contemporary drinks in Rungkut Kidul Village, with a focus on local beverage businesses. The survey method was used to collect data from respondents consisting of contemporary beverage consumers in the area. The variables observed include the level of consumer knowledge of the brand, brand awareness, and their perception of the quality and value of the local drink. Analysis was carried out using a descriptive statistical approach to describe respondent profiles and brand awareness. The results are expected to provide an in-depth understanding of the extent to which these local drinks are known and appreciated in the Rungkut Kidul environment. It is hoped that the findings from this research can provide guidance for local beverage business owners in improving their marketing strategies, as well as contributing to the development of local businesses in the face of increasingly fierce market competition.